Rancang Bangun Sistem Informasi Agenda Kerja Pimpinan dengan menggunakan Star Life Cycle Model (Studi Kasus : Universitas Jambi) - sebastian, widianto (Prodi Sistem Informasi FST Universitas Jambi, 2022)
A leader has duties and responsibilities in carrying out various kinds of work for his position in the office. The conventional way to manage the work agenda sometimes causes a mismatch in the management of the activity schedule, which most of the time is caused by human error. Therefore, an efficient and effective information system is needed to solve that problem. The Leader's Work Agenda Information System is a web-based information system that is used to manage various information regarding the leader's work agenda and appointments effectively in accordance with the procedures set at Jambi University. This is a software development research that uses the star life cycle development model, in which involves users in every stage of the development process. In every stage of the development process, the users' feedback is needed to make sure the end product meets users' requirements. In this study, software testing will also be conducted to see the errors that occur during and after the development. The testing is conducted using the black box method, where the testing focuses on functional testing to see whether the system can run as expected.